The Role Of Communication Psychology In Forming The Character Of Islamic Children - Nurul Fajar; Kusmawati Hatta; Zulkifli; Shahira Ulfa; Nursa’adi Ibrahim (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
Information openness in today's digital era allows a variety of information to be easily accessed by everyone, including children who do not yet have sufficient skills to sort through information properly. The development of a child's character is influenced by the family's treatment of him. Psychology of Communication in Islamic educational activities plays an important role to express intent with the communicant. Personnel in internal education, both educators or education staff, and students, of course, interact. The communication process that is not based on psychology, what will happen in life is disharmony or incompatibility. This research is qualitative research that describes all the data found through the literature approach. In previous research, there were several journals related to this research, some of which were about Islamic-Based Character Education through the Love of the Prophet Program for Kindergarten Children written by Iske Diana Towoliu, Sofia Hartati, Hapidin from the State University of Jakarta. The family is the smallest social system in which it can consist of father, mother, and children, each of whom has a role. Children have critical thinking about many things starting when they begin to recognize the language. The questions that come out of the mouth of a child should be answered with honest answers and can satisfy the child's heart. Moral education and honesty for a child start from the family, through parents.